Two new Dikraneurini genera from Ecuador (Hemiptera: Cicadellidae: Typhlocybinae) - Catalano, María Inés; Dietrich, Christopher H. (Zootaxa, 2017)
Two new genera, Sakakidikra n. gen. and Tricella n. gen., of tribe Dikraneurini McAtee are described from Ecuador, each based on a single new species, Sakakidikra jazminae n. sp. and Tricella antonellae n. sp. Both new genera described have only three apical cells in the forewing, an unusual characteristic in Typhlocybinae, but given the differences in the forewing and hind wing venation and male genitalia characters we consider it more appropriate to place the specimens in two separate monotypic genera.